Revisiting the critical weight hypothesis for regulation of pubertal timing in boys - Bygdell, Maria (Am J Clin Nutr, 2020)
BACKGROUND: Recent findings indicate that there is a body weight–sensing homeostatic regulation of body weight in postpubertal rodents and humans. It is possible that body weight sensing also might be involved in the regulation of pubertal timing. Although an early small study suggested that there is a critical body weight for pubertal timing in girls, most studies have focused on BMI and reported an inverse association between BMI and pubertal timing. OBJECTIVES: In the present longitudinal well-powered cohort study, we revisited the critical weight hypothesis and tested if prepubertal body weight is a more robust inverse predictor of pubertal timing than prepubertal BMI in boys. METHOD: We included men born during 1945–1961 (old cohort; n = 31,971) and men born during 1981–1996 (recent cohort; n = 1465) in the large BMI Epidemiology Study (BEST) Gothenburg (combined BEST cohort n = 33,436). Men with information on prepubertal body weight and BMI at 8 y of age and age at peak height velocity (PHV; an objective measure of pubertal timing) were included. RESULTS: Body weight explained more of the variance in age at PHV than BMI in both the old cohort and the recent cohort (combined cohort, body weight 6.3%, BMI 3.6%). Both body weight (β: −0.24 SD/SD increase in weight; 95% CI: −0.25, −0.23) and BMI (β: −0.18 SD/SD increase in BMI, 95% CI: −0.19, −0.17) were inversely associated with age at PHV but the association for body weight was significantly more pronounced than the association for BMI (P < 0.001). CONCLUSIONS: In conclusion, prepubertal body weight is a more robust inverse predictor of pubertal timing than prepubertal BMI in boys. We propose that body weight sensing constitutes a feedback mechanism to regulate pubertal timing.